Peran BMT Nusantara Umat Mandiri Dalam Mendorong Inklusi Lembaga Keuangan Syariah Non-Bank di Tulungagung - Khairan; Sodiq, Ahmad (Universitas Islam Tribakti Lirboyo Kediri, 2025)
ABSTRACT Purpose – This study discusses the role and challenges of BMT Nusantara UMAT MANDIRI in encouraging the inclusion of non-bank Islamic financial institutions in Tulungagung. As a Sharia-based microfinance institution, BMT has a strategic role in providing more inclusive financial access for people who have not been reached by the conventional banking system, especially MSMEs and lower-middle economies.Design/Methods – This research uses a qualitative approach with operational steps that need to be done; determine the focus and objectives of the research and prepare a research design. Data collection in the field through direct observation, in-depth interviews and documentation studies. The process of data analysis through several stages including; Data Reduction, Categorization, Data Interpretation, and concluding research results based on the data obtained.Findings – The results showed that BMT Nusantara UMAT MANDIRI contributed to improving access to Islamic finance, supporting the growth of MSMEs, and encouraging a culture of saving and financial planning through various Sharia contract-based products, such as Murabaha, Mudharabah, Musharakah, and Ijarah for financing, as well as Time Deposits, Umrah deposits, and Hajj deposits for deposit products. In addition, BMT also offers financing alternatives that are more ethical and equitable than conventional interest-based systems. Originality/Value – BMT Nusantara UMAT MANDIRI has a crucial role in strengthening Sharia financial inclusion in Tulungagung. However, to develop optimally and sustainably, BMT needs to continue to adapt to existing challenges through strengthening the system, innovation, and increasing Sharia financial literacy in the community.Keywords: BMT, Islamic financial inclusion, MSMEs, Islamic financing